(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
This article explores the concepts of denotative and connotative meanings in the English language. Words carry not only their literal meaning but also additional emotional, cultural, and social associations. The article defines both types of meaning, explains their differences, and illustrates them with examples.